2020
DOI: 10.1038/s41467-019-13999-1
|View full text |Cite
|
Sign up to set email alerts
|

Reversible manipulation of the magnetic state in SrRuO3 through electric-field controlled proton evolution

Abstract: Ionic substitution forms an essential pathway to manipulate the structural phase, carrier density and crystalline symmetry of materials via ion-electron-lattice coupling, leading to a rich spectrum of electronic states in strongly correlated systems. Using the ferromagnetic metal SrRuO 3 as a model system, we demonstrate an efficient and reversible control of both structural and electronic phase transformations through the electric-field controlled proton evolution with ionic liquid gating. The insertion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 42 publications
7
91
0
1
Order By: Relevance
“…Although several independent studies reported indications of THE and associated skyrmions in ultrathin layers of ferromagnetic SrRuO 3 via transport measurements, [ 34,41,154,156,157,171–173 ] while these indications are questioned by other models very recently. [ 174–181 ] For instance, both Kan et al.…”
Section: Topological Structures In Magnetic Thin Films and Heterostrumentioning
confidence: 99%
See 1 more Smart Citation
“…Although several independent studies reported indications of THE and associated skyrmions in ultrathin layers of ferromagnetic SrRuO 3 via transport measurements, [ 34,41,154,156,157,171–173 ] while these indications are questioned by other models very recently. [ 174–181 ] For instance, both Kan et al.…”
Section: Topological Structures In Magnetic Thin Films and Heterostrumentioning
confidence: 99%
“…THE signal was also observed in other functional oxide thin films and heterostructures, as shown in Table 1. [ 34,155–157,166,167,169,172,177,182,183 ] For instance, the magnitude of ρ THE in the ferromagnet EuO thin films can reach up to 12 µΩ cm at 50 K, nearly two orders of magnitude larger than that in SrRuO 3 . [ 167 ] Furthermore, Vistoli et al.…”
Section: Topological Structures In Magnetic Thin Films and Heterostrumentioning
confidence: 99%
“…275 Similar reversible phase transformations mediated by hydrogen and oxygen ions was also observed in VO 2 , ZnO, WO 3 , SrRuO 3 , La 1Àx Sr x MnO 3 , La 0.7 Sr 0.3 MnO 3 /SrIrO 3 superlattice films, etc. 18,164,[276][277][278][279][280][281] Water was also used as a gating medium for achieving hydrogen doping. 282 The ionization of water to form H + and OH À occurs when a bias voltage over 1.23 V is applied between an electrode and TMOs in water.…”
Section: Photo-electrocatalyst and Electrocatalystsmentioning
confidence: 99%
“…4b , when the gate voltage increases (shifts the Fermi energy towards the negative values), the strength of DMI becomes larger. Besides the gate-induced change of carrier density, the proton intercalation may locally form proton concentration gradient which can also lead to the SIS breaking and contribute DMI 34 . Specifically, the DMI at is about twice of the value at .…”
Section: Discussionmentioning
confidence: 99%